When Fear Overshadows Perceived Plausibility: The Influence of Incongruencies on Acrophobia in VR - Brubach, Larissa; Celikhan, Deniz; Ruffert, Lennard; Westermeier, Franziska; Latoschik, Marc Erich; Wienrich, Carolin (Proceedings (IEEE Conference on Virtual Reality and 3D User Interfaces. Online), 2025)
Virtual Reality Exposure Therapy (VRET) has become an effective, customizable, and affordable treatment for various psychological and physiological disorders. Specifically, it is used to treat specific anxiety disorders, such as acrophobia or arachnophobia, for decades. However, to ensure a positive outcome for patients, we must understand and control the effects potentially caused by the technology and medium of Virtual Reality (VR) itself. This article specifically investigates the impact of the Plausibility illusion (Psi), as one of the two theorized presence components, on the fear of heights. In two experiments, 30 participants each experienced two different heights with congruent and incongruent object behaviors in a 2 x 2 within-subject design. Results show that the strength of the congruence manipulation plays a significant role. Only when incongruencies are strong enough will they be recognized by users, specifically in high fear conditions, as triggered by exposure to increased heights. If incongruencies are too subtle, they seem to be overshadowed by the stronger fear reactions. Our evidence contributes to recent theories of VR effects and emphasizes the importance of understanding and controlling factors potentially assumed to be incidental, specifically during VRET designs. Incongruencies should be controlled so that they do not have an unwanted influence on the patient's fear response.